PENGARUH KEMAMPUAN INDIVIDUAL DAN NORMA SUBYEKTIF TERHADAP MINAT UMKM SE KOTA MALANG UNTUK MENGGUNAKAN ZAHIR ACCOUNTING SOFTWARE DALAM MEMBUAT LAPORAN KEUANGAN - Siti Aisya; Noor Shodiq Askandar; Afifudin Afifudin (Universitas Islam Malang, 2019)
ABSTRACTMicro, small and medium enterprises are business behaviors that are engaged in various business fields, which touch the interests of the community. UMKM have complex transactions ranging from data collection, management to the provision of accounting information. So that the computerized system that includes the purchasing system, the sales system will be very helpful, when compared to manual systems. This requires UMKM employees to be able to carry out Zahir computer-based financial reports to be more efficient and practical. The purpose of this study was to find out and understand and use the individual abilities of UMKM in using Zahir in making reports and the existence of subjective norms for the interest of UMM in Malang to use Zahir Accounting in making financial reports. 58 employees in the accounting section of UMKM actors in Malang City. The techniques for collecting data using survey methods with questionnaires. This research was tested with several statistical tests consisting of descriptive statistical tests, data quality tests, classic assumption tests and hypothesis tests. The results showed that individual abilities influence the interest of UMKM in using Zahir Accounting software because in making financial statements can be easier and more efficient, subjective norms (perceptions) positively influence interest in using Zahir Accounting software, accounting knowledge has a significant effect on interest in using Zahir software because increasing employee interest in using Zahir Accounting software. Keywords: individual abilities, subjective norms, UMKM interests, Zahir Accounting